Acetate as a potential feedstock for the production of value-added chemicals: Metabolism and applications - Kim, Yeonhee; Lama, Suman; Agrawal, Deepti; Kumar, Vinod; Park, Sunghoon (Elsevier, 2021)
Acetate is regarded as a promising carbon feedstock in biological production owing to its possible derivation from C1 gases such as CO, CO2 and methane. To best use of acetate, comprehensive understanding of acetate metabolisms from genes and enzymes to pathways and regulations is needed. This review aims to provide an overview on the potential of acetate as carbon feedstock for industrial biotechnology. Biochemical, microbial and biotechnological aspects of acetate metabolism are described. Especially, the current state-of-the art in the production of value-added chemicals from acetate is summarized. Challenges and future perspectives are also provided.
Keywords: Acetate; Value-added chemicals; Metabolism; Regulations; Tolerance